2017
DOI: 10.1371/journal.pone.0172839
|View full text |Cite
|
Sign up to set email alerts
|

The use of mesoscale eddies by juvenile loggerhead sea turtles (Caretta caretta) in the southwestern Atlantic

Abstract: Marine animals, such as turtles, seabirds and pelagic fishes, are observed to travel and congregate around eddies in the open ocean. Mesoscale eddies, large swirling ocean vortices with radius scales of approximately 50–100 km, provide environmental variability that can structure these populations. In this study, we investigate the use of mesoscale eddies by 24 individual juvenile loggerhead sea turtles (Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 46 publications
1
27
1
Order By: Relevance
“…The capacity of eddies for trapping ocean water and to generate vertical movements inside their cores (Barceló‐Llull et al, ; Gaube et al, ) also has biological implications. It has been shown that mesoscale eddies are able to concentrate phytoplankton in their interiors (Chelton, Gaube, et al, ; Gaube et al, ; Liu et al, ) and consequently gather all trophic levels (Gaube et al, ; Godø et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of eddies for trapping ocean water and to generate vertical movements inside their cores (Barceló‐Llull et al, ; Gaube et al, ) also has biological implications. It has been shown that mesoscale eddies are able to concentrate phytoplankton in their interiors (Chelton, Gaube, et al, ; Gaube et al, ; Liu et al, ) and consequently gather all trophic levels (Gaube et al, ; Godø et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…50–100 km) to quantitatively link animal movements with specific mesoscale oceanographic features 18 . Yet these features are likely to have profound effects on ocean ecology if large pelagic fishes are able to detect the presence of favorable conditions associated with mesoscale eddies and to adjust their horizontal and vertical movements to increase interactions with prey, as has been shown for marine mammals 19 , seabirds 20 , and turtles 21 , 22 . However, relatively little is known about collocation of pelagic fish movements with mesoscale oceanographic features.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoscale eddies are energetic entities that structure open ocean ecosystems on time scales of weeks to months and spatial scales of tens to hundreds of kilometers (4). Eddy processes at these scales provide controls on biogeochemical fluxes (4, 5) and affect biological communities, including lower trophic levels (68), marine mammals (912), birds (13), turtles (14, 15), and fishes (16). Coupling of biology and ocean physics at the mesoscale has, in some cases, identified specific features as “hotspots” of biological activity, spanning trophic levels from primary producers (1720) to zooplankton and small fish (21), up to large pelagic fish (22, 23).…”
mentioning
confidence: 99%